The Correlation Between Working Period and Total Immunoglobulin E (IgE) in Textile Industry Workers - Putri, Winanti Wahyuning; Saktiningsih, Hari (Jurnal Biologi Tropis, 2026)
Exposure to chemical substances in the textile industry may cause occupational health problems, particularly allergic and immunological disorders mediated by Immunoglobulin E (IgE). Prolonged exposure to textile chemicals can increase the risk of allergic sensitization, which is characterized by elevated total IgE levels in the blood. This study aimed to determine the relationship between work duration and total Immunoglobulin E (IgE) levels among textile industry workers. This study used an analytical observational method with a cross-sectional design. A total of 15 textile industry workers who met the inclusion and exclusion criteria were included as respondents. Data on work duration were obtained through interviews, while total IgE levels were measured by laboratory examination using the Electrochemiluminescence Immunoassay method. Data analysis was performed using the Spearman correlation test with a significance level of p < 0.05. The results showed a significant relationship between work duration and total IgE levels (p < 0.001) with a very strong positive correlation (r = 0.943). Workers with longer work duration tended to have higher total IgE levels. In conclusion, work duration is significantly associated with increased total IgE levels as an indicator of allergic immune response in textile industry workers.